Pengaruh Budaya Organisasi, Motivasi Kerja Dan Kepuasan KerjaTerhadap Produktivitas Kerja Pada Karyawan Titik Terang Konveksi Yogyakarta - Lemba, Maria Della Strada; Herawati, Jajuk (Jurnal Manajemen DIVERSIFIKASI, 2022)
This research was conducted to examine the influence of organizational culture, work motivation, job satisfaction on employee productivity, the employess of Titik Terang Konveksi Yogyakarta. The population in this study amounted to 45 employees. The sample of this study used the census method, so the research sample was determined as many as 45 employees covering all employees. This study uses a quantitative approach, the data for this study were obtained through a research questionnaire that had been filled in by the respondents who had been determined. The data analysis method used is multiple linear regression analysis method with the help of the test instrument spss version 23.0. The results of this study indicate that there is a positive and significant effect of job satisfaction on work productivity, there is a positive and significant effect of work motivation on work productivity, there is a positive and significant effect of job satisfaction on work productivity. And with the results of the f test (Goodness of fit) states that organizational culture, work motivation, job satisfaction simultaneously have a positive and significant effect on work productivity the employess of Titik Terang Konveksi Yogyakarta Keywords: Organizational Culture, Work Motivation, Job Satisfaction and Word Productivity